A novel approach of branch-line coupler via parallel transmission line and DGS - Sadegh Heydari Kahkesh; Akram Sheikhi (Scientific Reports)
Abstract This article presents the design, simulation, and experimental validation of an ultra-compact 3-dB microstrip coupler with significantly reduced dimensions. The primary objective of this study is to develop a miniaturized coupler while maintaining high performance in terms of return loss, insertion loss, and phase balance. To achieve this, the proposed design employs parallel transmission lines, where shorter lines are directly integrated into the circuit, and longer lines are implemented as spiral structures to optimize space utilization. Additionally, a defected ground structure (DGS) is incorporated to further reduce the coupler’s footprint and facilitate the implementation of high-impedance transmission lines. Since high-impedance microstrip lines require extremely narrow widths that are impractical due to fabrication constraints, the use of DGS effectively addresses this challenge by modifying the ground plane to achieve the desired impedance characteristics. The proposed coupler operates at a center frequency of 2.3 GHz and achieves a 75% size reduction compared to conventional designs. Experimental results demonstrate a return loss of approximately − 15 dB, a fractional bandwidth (FBW) of around 10.5%, and a consistent $$90^°$$ phase difference between output ports across a wide frequency range. The agreement between mathematical analysis, full-wave simulations, and fabricated prototype measurements validates the effectiveness of this approach. The compact size, minimal losses, and excellent phase and magnitude balance make this design a strong candidate for modern wireless communication and RF applications requiring high integration and efficiency.